Pengaruh Faktor Uncertainty Avoidance, Perceived Influence, Perceived Economic Value terhadap Startup Intention pada Mahasiswa Teknik dan Non-Teknik - Abdurrahman Zain Hamim; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Based on data obtained from BPS, the number of working-age residents (15 years) continues to increase. Students of working age are included in the working age and are considered crucial because they can be actors of change in the surrounding environment. However, this becomes difficult because of the paradigm of office workers who are considered more by the community than by their own efforts. Changing the mindset is not easy, there are several influencing factors such as cultural factors, namely uncertainty avoidance, perceived influence and perceived economic value of the startup itself which can affect startup intention. The sample used was 195, sample selection using the proportionate random sampling method. After collecting data, it is analyzed by descriptive statistical methods and testing of basic assumptions including normality tests, linearity tests and homogeneity tests, from the test results can be formed non-parametric analysis methods to determine the relationship between variables. The results of the descriptive analysis show that the mean value of all variables is very high. And from the results of non-parametric analysis, it shows that all variables have a significant influence.